Public Affairs Index: governance in the States of India - Mathew, C. K.; Mukunthan, Athreya; Divekar, Vivek (Bangalore, 2016)
The Public Affairs Index (PAI) is an attempt to bring together the states of the country which are culturally, economically and socially diverse, into a common data-driven framework, to facilitate an interstate comparison.
Keywords: Public Administration; Public Affairs; IAS as an author